A historico-cultural trail of cultural distance in intercultural postcolonial relations: between the Igbo African and GermanEuropean Cultures (2013)
Cultural Distance (CD), the mean of proximity and distance resultant from cultural difference, is critical to intercultural postcolonial relations of asymmetry and textual interpretive practices like translation, media imaging of the other and the like. This is because it potentially affects interpersonal, intergroup, business and interstate relations. It can also affect the understanding of cultural text units, images and contexts, as well as attitude to and reception of the otherness of the culturally different. Whereas CD has been measured by variables subjected to mathematical calculations, this paper used the spatial and temporal convergence and divergence between the Igbo African and the German European cultures as a subset ol that between Europe and Africa in general. Adopting a historical comparative and textual analyses of data, it suggests a view oi CD in an intercultural postcolonial context between Europeans and Africans in the relations of Europeans to their traditional pasts and to the African traditional cultural other.